(untitled) (Transport systems and technologies, 2022)
In order to develop corporate culture in the Ukrainian railway subdivisions, this article analyzes the empirical research of the psychological working climate at the regional branch of «South-Western Railway» JSC «Ukrainian Railways». The empirical research was conducted in the form of a questionnaire, based on three methods: assessment of the psychological atmosphere in the team (according to A. F. Fiedler), determination of the index of group cohesion (K. E. Sishor), assessment of job satisfaction (V. A. Rozanova). The research results showed the level of work satisfaction of employees of the selected unit (specialists in transport technology) for various factors.